The Effect of Different Levels of Dietary Phosphorus (Inorganic Phosphorus) on Performance in Broiler Chicks - Moghadam, A. Nouri (International Journal of Poultry Science, 2006)
This experiment was conducted to study the effects of available phosphorus on the growth performance, phosphorus and calcium metabolism of broiler chicks. Four hundred and five 7 days old age chicks were fed with a diet containing 0.20, 0.25, 0.30% available phosphorus (0.30, 0.35 and 0.40 % respectively total phosphorus) in a completely randomized design, consisting of 45 chicks per replicate during a 14 days experimental period (from 8 to 21 days of age). All feeding programs were isocaloric and isoprotein. chicks were put at random into 3 treatment groups (3 replicates and 135 chicks per treatment).The effects of different levels of available phosphorus on body weight, daily feed consumption, feed conversion efficiency, feed/gain ratio, weight percentage of body parts, percentage of bone ash, calcium and phosphorus percentages in bone ash, and plasma inorganic phosphorus and calcium were assessed and determined. The results showed that the effects of different levels of available phosphorus on body weight, daily feed consumption, bone ash percentage, plasma calcium and phosphorus percentages (p< 0.01) and bone ash phosphorus percentage (p< 0.05) were significant while no significant effects were observed in the case of feed conversion efficiency, feed/gain ratio, and plasma calcium. From the results obtained, it seems that increasing levels of inorganic phosphorus (non-phytate phosphorus) led to more efficiency in the broiler performance, calcium and phosphorus utilized by poultry.